PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN NASABAH PADA PT BPR DANA NAGOYA - Meryanti, Meryanti; Purba, Tiurniairi (Universitas Sam Ratulangi, 2020)
This study aimed to determine the effect of service quality and promotion on customer satisfaction also this study took place at PT BPR Dana Nagoya in Batam City. Data analysis technique that was used is multiple linear methods. An operations research design used is descriptive analysis. In this study test already consists of validity, reliability, classic assumption test, multiple regression analysis, and coefficient of determination, t-test and f-test. Sampling has been developed through purposive sampling, consist of 116 respondents. Data has been collected by main instrument of questionnaire. Based on results test through multiple regression analysis shown the service quality has an effect towards customer satisfaction of 44.5% and promotion has an effect of 22.3% on customer satisfaction. Coefficient of determination has analysis for R2 of 74.5% while remaining result 25.5% influenced by another variables. The results of research indicate that there is a positive and significant impact for service quality to customer satisfaction, there is a positive effect of promotion for customer satisfaction and have positive also significant effect partially or simultaneously on customer satisfaction at PT BPR Dana Nagoya.Â Keywords: Customer Satisfaction; Promotion; Service Quality.